Strategi Perumda Pasar Sewakadarma Kota Denpasar Dalam Pencapaian Target Penerimaan E-Retribusi Pasar Di Pasar Badung. - Kirani, Gusti Ayu Pudak Chandra; Prabawati, ⁠Ni Putu Anik; Wirantari, ⁠I Dewa Ayu Putri (Socio-political Communication and Policy Review, 2025)
This study aims to analyze and provide recommendations for improving strategies in increasing e-retribution revenue to achieve market retribution targets in Badung Market. This study uses a qualitative method with a descriptive approach. The data sources for this study come from primary and secondary data collected through purposive sampling techniques. Data were collected through interviews, observations and documentation. The results of this study are explained using Wheelen and Hunger strategy of management strategy which includes four stages: (1) Environmental Observation, (2) Strategy Formulation, (3) Strategy Implementation, (4) Evaluation and Control. The results of the analysis show that the strategy of Perumda Pasar Sewakadarma, Denpasar City in achieving the target of market e-retribution revenue is not optimal, this is due to market e-retribution revenue has not reached the target that has been determined in Badung Market. In addition, the SWOT (Strength, Weakness, Opportunity, Threat) analysis by Freddy Rangkuti highlights the strength of Perumda in utilizing regulations and the availability of human resources, as well as capable facilities and infrastructure, opportunities in the market e-retribution acceptance system by traders, and challenges in overcoming the quiet conditions of the Badung market which results in stall sellers not selling. Recommendations from this study include the Strength-Opportunity: Optimizing Socialization and Technical Guidance on the implementation of e-retribution in Badung Market in a circular manner, Weakness-Opportunity Strategy: Improving coordination and communication in the division of tasks for implementing e-retribution in the market by utilizing the new Culinary Market in Badung Market, Strength-Threat Strategy: Relying on competent human resources to overcome the competitiveness of shops around Badung Market and the rise of online shopping through massive and specific social media promotions, Weakness-Threat Strategy: Conducting regular socialization regarding education on saving retribution to minimize traders who do not pay market retribution.